2003
DOI: 10.1002/pssa.200306474
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in porous silicon during annealing

Abstract: Porous silicon can be used as separation layers in layer transfer technology where a thin layer of crystalline silicon is separated from a large wafer and transferred onto a cheap foreign substrate. The porous layers are part of the fabrication process and undergo the processing treatment, especially the thermal treatments. We have analyzed by transmission electron microscopy the structural development of porous silicon layers in dependency of annealing and layer preparation conditions. The fabrication of sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…[34] In fact, from low-porosity (f < 0.5) etched nano-PS layers, having open-pores (especially dendritic pore channels or spongy like structure), it has been shown that after an annealing process during several ten of minutes (20-120 min) at temperatures from 800 to 1300 K in a controlled atmosphere: (i) the pore channels changed to closed non-overlapped pores. The pores in the bulk are enlarged while those at the surface are closed.…”
Section: Annealed Porous Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] In fact, from low-porosity (f < 0.5) etched nano-PS layers, having open-pores (especially dendritic pore channels or spongy like structure), it has been shown that after an annealing process during several ten of minutes (20-120 min) at temperatures from 800 to 1300 K in a controlled atmosphere: (i) the pore channels changed to closed non-overlapped pores. The pores in the bulk are enlarged while those at the surface are closed.…”
Section: Annealed Porous Siliconmentioning
confidence: 99%
“…Moreover, increasing the duration and/or the annealing temperature increases the pore size and modifies the shape from elongated pores (annealing at 880 K), spherical pores (annealing around 1000 K) to facetted pores (annealing above 1070 K). [34,35] Until now, few experimental data of thermal conductivity of annealed-PS are available in literature. Recent study performed on thick porous freestanding layer by Wolf and Brendel [10] using lock-in thermography reports the room temperature thermal conductivities for porosity from 0.27 to 0.66.…”
Section: Annealed Porous Siliconmentioning
confidence: 99%
“…The results of the thermal annealing were not significant with regards to stabilization, but coarsening of the PSi structure during the annealing in inert ambient conditions was an interesting observation. This enables the modification of the pore size distribution after the anodization, which was an exploitable finding regarding drug delivery applications [48][49][50]. While some results of the chemical derivations of the PSi surface with organic compounds and formation of Si C bonds were already reported previously [51][52][53][54][55], the reports by the group of Buriak finally confirmed the advantages of Si C bond in the stabilization [55][56][57].…”
Section: Chemical Surface Modificationsmentioning
confidence: 54%
“…[ 55 ] Conventional thermal oxidization of PSi is carried out at 500-900 °C for durations of several minutes to an hour, [ 11,52,[56][57][58][59] primarily to improve the nanostructure stability in aqueous media. Oxidation at temperatures higher than 1000 °C leads to structural deterioration of the porous layer, accompanied by drastic decrease in the surface area and transition of the elongated columns into closed sphere-like pores; [60][61][62] thus unsuitable for biosensing applications. Indeed, we found that oxidation at temperatures above 1010 °C caused severe structural changes (see Figure S1, Supporting Information), resulting in a drastic decrease in the thickness and the porosity of the porous layer, and eventually collapse of the nanostructure.…”
Section: Fabrication and Functionalization Of Oxidized Psimentioning
confidence: 99%